2019
DOI: 10.1111/cobi.13317
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and minimizing environmental impacts of the Belt and Road Initiative

Abstract: China's Belt and Road Initiative (BRI) sets to create connections and build infrastructure across Eurasia, Asia, and parts of the African continent in its initial phase and is the largest infrastructure project of all time. Any infrastructure project on this scale will necessarily pass through ecofragile regions and key biodiversity areas (KBAs). This creates an imperative to identify possible areas of impact and probable effects on conservation values to facilitate adaptive planning and to mitigate, minimize,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 33 publications
2
91
0
1
Order By: Relevance
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
“…Afghanistan is not only one of the most fragile and conflict-afflicted states in the world, but is also a country that seeks economic cooperation facilitated through political trust, economic integration, business collaboration, and cultural and humanistic communication [1]. In the past decade, more than 3200 commercial initiatives have been constructed [2]. This is in accordance with the tendency toward globalization, which facilitates an international community that coordinates well with the interests of sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Another policy to minimize road impacts on tigers and other wildlife would be to require Chinesefunded BRI efforts overseas to ascribe to the same strict environmental regulations on road development that now exist within Chinese borders (14). Likewise, national bodies and international funding agencies, such as the Asian Development Bank and World Bank, should mandate international oversight and standards on environmental impact assessments (14). Our results highlight the need to make sustainable road development a top priority.…”
Section: Discussionmentioning
confidence: 90%
“…The creation of bilateral agreements that include provisions for reducing wildlife poaching and trafficking between China and countries that are part of the BRI would also lessen the impacts of that infrastructure initiative on tigers and other species of conservation concern (8). Another policy to minimize road impacts on tigers and other wildlife would be to require Chinesefunded BRI efforts overseas to ascribe to the same strict environmental regulations on road development that now exist within Chinese borders (14). Likewise, national bodies and international funding agencies, such as the Asian Development Bank and World Bank, should mandate international oversight and standards on environmental impact assessments (14).…”
Section: Discussionmentioning
confidence: 99%
“…But they would Box 1: Net outcomes on the Belt and Road Some 75% of the infrastructure that will exist on the Earth by 2050, by investment, has yet to be built [14]. One component of this coming infrastructure boom, China's 'Belt and Road Initiative' (BRI; Extended Data Figure 1), will build cultural and trade links across the world, but is likely to exacerbate biodiversity losses [15,16]. Imagine that the BRI sought, instead, to achieve a net positive outcome for biodiversity.…”
Section: Implementing a Net Outcomes Approachmentioning
confidence: 99%